Modernization in Ghana and the U.S.S.R.: a comparative study - Dowse, Robert Edward (London : Routledge & K. Paul, New York : Humanities P., 1969)
The book contains some aspects of the politics of modernization in two states, the U.S.S.R. and Ghana. One of the major contentions of this volume is that they faced a variety of similar problems and that their responses to these had a great deal in common. There are also a large number of striking similarities concerning attitudes to economic development and the outside world.
Bibliography: p. 104-107.
usc 25/01/2019
Loans
Keywords: Politics and government; Soviet Union; Economic history; Ghana; Soviet Union